KONSEP INTEGRASI ILMU DAN AGAMA SERTA GAGASAN ISLAMISASI ILMU PENGETAHUAN - Solihin (Kaffah: Jurnal Pendidikan dan Sosio Keagamaan, 2023)
Abstract Abstract This research is intended to explore the concept of integration of science and religion as well as the idea of Islamization of science so that it becomes one of the basics for perfecting the design of Islamic Education in Indonesia. The relationship between religion and science is not always harmonious, as explained by Barbour, a scientist who researches and classifies the relationship between science and religion into four approaches, namely conflict, independence, dialogue and integration. All four are based on the premise that both science and religion recognize each other's cognitive claims in descriptions of the physical realm. The connection with the concept of integration is the idea of the Islamization of science considering that so far knowledge (science) has been viewed as neutral, universal and value-free. It is important to examine both of these problems in order to find their benefits for the development of Islamic Education as stated in the results of this study.